2006
DOI: 10.1007/s10633-006-9005-1
|View full text |Cite
|
Sign up to set email alerts
|

Congenital absence of optic chiasm: demonstration of an uncrossed visual pathway using monocular flash visual evoked potentials

Abstract: A 35 month old child was referred for electrophysiology testing with pendular nystagmus, corresponding head oscillations and reduced vision. Flash visual evoked potential (VEP) revealed large responses at the right occiput (but not the left occiput) from the right eye and similar large responses at only the left occiput from the left eye, indicating absent/deficient crossover at the chiasm. A magnetic resonance imaging (MRI) scan subsequently confirmed absence of the optic chiasm. There was no other evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In our previous study we showed that visual electrophysiological screening of infants with congenital nystagmus can establish or exclude retinal and postretinal pathway dysfunction [30]. Children with maldeveloped optic chiasm in this and other studies were electrophysiologically assessed due to their congenital nystagmus [4,6,8,9,31] or were suspected of having albinism [2]. Therefore, from previous studies and ours, we may assume that already in early infancy the distinctive VEP will help in the diagnosis of achiasmia.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In our previous study we showed that visual electrophysiological screening of infants with congenital nystagmus can establish or exclude retinal and postretinal pathway dysfunction [30]. Children with maldeveloped optic chiasm in this and other studies were electrophysiologically assessed due to their congenital nystagmus [4,6,8,9,31] or were suspected of having albinism [2]. Therefore, from previous studies and ours, we may assume that already in early infancy the distinctive VEP will help in the diagnosis of achiasmia.…”
Section: Discussionmentioning
confidence: 63%
“…Achiasmia can appear as an isolated abnormality [1,2,5,6,8,9] or as a part of septooptic dysplasia with a constellation of small anterior visual pathways, absence of the septum pelucidum, thinning of the corpus callosum and possible other abnormalities of pituitary gland, hemispheric migration anomalies and perinatal hemispheric injury [3,4,7]. In child 1 the MRI results confirmed lack of connection between both hypoplastic optic nerves and tracts as an isolated abnormality.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…One study noted an asymmetrical optic chiasm, possibly due to optic nerve aplasia (Taylor 2005). Unilateral or bilateral absence of the optic chiasm presented as one of three types, where nasal-retinal fibers would not decussate to the contralateral hemisphere (Taylor 2005(Taylor , 2007Brown et al 2006;Biega et al 2007). These were classified as the following: type 1: reduced decussation, normal appearing optic nerves; type 2: reduced decussation chiasmal hypoplasia, midline defects (septo-optic dysplasia); and type 3: reduced decussation, chiasmal hypoplasia, clefts, and agenesis of corpus callosum.…”
Section: Optic Nerve (Cn Ii)mentioning
confidence: 99%